Ответы и объяснения

  • NO3
  • хорошист
2013-08-11T11:55:38+04:00
1) (5x-2)/4-((x^2+3x-1)/3)=-1,   
(15x-6-4x^2-12x+1)/12=-1,   
 (-4x^2+3x-5)=-12,     
-4x^2+3x+7=0,     
4x^2-3x-7=0,     
D= (-3)^2-4*4*(-7)=9+112=121   
x1=(3+11)/8=14/8=7/4=1,75     
x2=(3-11)/8=-1
-----------------------------------------------
2) 0,5a^2-0,3a=1,3a-0,3   
  0,5a^2-1,6a+0,3=0 
   a^2-3,2+0,6=0   
  D=(-3,2)^2-4*0,6=10,24-2.4=7,84
x1=(3,2+2,8)/2=3
x2=(3,2-2,8)/2=0,2 
------------------------------------------------------
3) b=-3, D=17, a=1.
 D=b^2-4*a*c, => 17=9-4*1*c
 17=9-4c
 4c=9-17
 4c=-8
 c=-2
a^2+3b-2=0